2002
DOI: 10.1128/jcm.40.8.2746-2749.2002
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal Lactobacillus Flora of Healthy Swedish Women

Abstract: Species of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
227
3
8

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(258 citation statements)
references
References 28 publications
20
227
3
8
Order By: Relevance
“…Our results are in general agreement with other studies (17,19,20) showing that only one or a few Lactobacillus species colonize the healthy human vagina (1.94 species/individual) and that species within the L. acidophilus complex predominate (L. crispatus). Antonio et al (21) (20) found that L. crispatus was the only Lactobacillus species linked to a single grade (as determined by Gram stain-based grading of vaginal smears), namely grade Ia, while the other lactobacilli were more evenly distributed over all specimens.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our results are in general agreement with other studies (17,19,20) showing that only one or a few Lactobacillus species colonize the healthy human vagina (1.94 species/individual) and that species within the L. acidophilus complex predominate (L. crispatus). Antonio et al (21) (20) found that L. crispatus was the only Lactobacillus species linked to a single grade (as determined by Gram stain-based grading of vaginal smears), namely grade Ia, while the other lactobacilli were more evenly distributed over all specimens.…”
Section: Discussionsupporting
confidence: 83%
“…Additionally, some Lactobacillus species, such as L. iners, do not grow on Rogosa or MRS media traditionally used for lactobacillus recovery (16). This species seems to be dominant both among white (17) and black women (18). However, due to its culture characteristic (growth only on blood agar), its antagonistic ability is not known.…”
Section: Discussionmentioning
confidence: 99%
“…iners is the predominant component of the vaginal microbiota in a significant proportion of healthy women (5,6,30,31). There is no clinical evidence to date that the presence of L. iners is associated with induction of discharge, inflammation, or discomfort.…”
mentioning
confidence: 99%
“…Первые данные о выделении L. iners у женщин без признаков нарушения микрофлоры вла-галища появились в 2002 г. [14]. Дальнейшие исследования показали, что данный вид часто встречается при БВ, обнаруживается у женщин с антенатальными потерями плода в анамнезе [15,16].…”
Section: вагинальный микробиомunclassified